A Survey on Medicinal Plants used by the Folk Medicinal Practitioners in Tangail Sadar Upazilla, Tangail, Bangladesh (Journal of Environmental Science and Natural Resources, 2015)
Medicinal plants form an important and often the only component in the formulations used by the folk medicinal practitioners of Bangladesh for treatment of various ailments. Folk medicinal practitioners, otherwise known as Kavirajes, perform an integral role in the delivery of primary health-care to substantial segments of both rural and urban population of the country. To get a comprehensive view of the medicinal plants of Bangladesh, it is therefore important to conduct extensive interviews of individual Kavirajes of both urban and rural areas. Towards obtaining such comprehensive information, the present ethno-medicinal survey was conducted among the Kavirajes of 15 randomly surveyed villages of Tangail Sadar Upazila in Bangladesh to document their use of medicinal plants and the ailments treated by those plants. Information was obtained from the Kavirajes with the help of a semi-structured questionnaire and the guided field-walk method. The results showed that the Kavirajes of the 11 villages surveyed used a total of 55 plants distributed into 35 families in their formulations. The Mimoceseae family provided 4 plants, while the Acanthaceae, Liliaceae, Lamiaceae and Fabaceae families provided 3 plants each. Mainly leaves were used for this purpose. Other plant parts roots and stems were also used. The various ailments treated included gastrointestinal disorders, cuts and wounds, fever, respiratory tract disorders, snake bites, pain, menstrual problems, physical weakness, diabetes, mental disorders, cardiovascular disorders, skin disorders, chicken pox, burns, spermatorrhea, bone fractures and cattle ailments.DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22141 J. Environ. Sci. & Natural Resources, 7(1): 35-39 2014